Comparing and analyzing the accuracy and stability of calculating SF6 tracer gas mixing results in mine tunnels using RNG model and DES model through experiments. - Fang Xu; Jian Liu; Dong Wang (PLoS ONE)
The tracer gas wind measurement method must measure the average concentration based on the known mixing distance of the tracer gas in order to accurately calculate the air volume. we established a T-shaped cross-ventilation duct with a square cross-sectional side of 0.3 m to simulate mine tunnels experimentally, and created the above duct model in Fluent software. Using the renormalization group (RNG k-ε) and detached eddy simulation (DES) models in Fluent to calculate the concentration and mixing distance of sulfur hexafluoride (SF6) tracer gas in air collection duct, and conducted SF6 blending experiments. In the first 7m stage of air collection duct, the SF6 mixing rate in the experiment was the fastest, while the RNG k-ε model was the slowest. However, after 7 meters, the mixing rate in the experiment rapidly slowed down, while there was no significant change in the RNG k-ε model. The rate of change of the DES model was between the above two results, but the concentration change was the most unstable. And the mixed distance results of the three were highly consistent. The results of this study provide a reference for selecting appropriate numerical simulation models for future calibration work of mine ventilation systems.